Fetal Outcome in Deliveries with Meconium Stained Liquor (Bangladesh Journal of Child Health, 2010)
Introduction: Meconium staining amniotic fluid is associated with lots of adverseoutcome and has long been considered to be a bad predictor of fetal outcome.Objective: This prospective observational study was undertaken to find out immediatefetal outcome in meconium stained liquor.Materials and Methods: This study was conducted in Obstetrics and Gynecologydepartment of Dhaka National Medical Collage Hospital from July to December 2008.The pregnant women with yellow, brown and thinly stained amniotic fluid in labour withgestational age 37 completed weeks were enrolled in the study. Their babies weretaken as case and followed upto 7 days after delivery in National Medical CollageHospital and in Dhaka Shishu Hospital after admission when required. Babies bornwithout meconium stained liquor were taken as a control.Results: Total 80 cases were enrolled in the study as case and 80 cases wereenrolled as control. Mean gestational age was 39.3±1.5 weeks in cases and 38.5±1.3weeks in control. There was 13.8% pregnancy induced hypertension in case groupand 3.8% in control group. Pre-eclampsia were present 10% in case group and 1.1%in control group (p